2019
DOI: 10.1177/1477370819850943
|View full text |Cite
|
Sign up to set email alerts
|

Crime scripting: A systematic review

Abstract: More than two decades after the publication of Cornish's seminal work about the scripttheoretic approach to crime analysis, this article examines how the concept has been applied in our community. The study provides evidence confirming that the approach is increasingly popular; and takes stock of crime scripting practices through a systematic review of over one hundred scripts published between 1994 and 2018. The results offer the first comprehensive picture of this approach, and highlights new directions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 103 publications
1
51
0
Order By: Relevance
“…Crime scripts have been proposed as a methodology to analyse relatively various categories of crimes (Cornish 1993;Borrion 2013;Dehghanniri and Borrion 2019). A crime script describes a sequence of steps involved in a specific crime: precursors, transactions, and the aftermath.…”
Section: Crime Scriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crime scripts have been proposed as a methodology to analyse relatively various categories of crimes (Cornish 1993;Borrion 2013;Dehghanniri and Borrion 2019). A crime script describes a sequence of steps involved in a specific crime: precursors, transactions, and the aftermath.…”
Section: Crime Scriptsmentioning
confidence: 99%
“…Crime script analysis has been used to study a wide range of specific crimes (Cornish 1993). Scripts have been applied relatively often to cybercrime and fraud, perhaps because these are often slightly more complex crimes (for a review see Dehghanniri and Borrion (2019)). In the present study, an important goal of our script is to gauge the amount of effort put into each specific form of fraud.…”
Section: Crime Scriptsmentioning
confidence: 99%
“…Although Dehghanniri and Borrion’s (2019) systematic review found the pool of existing crime scripts to cover a broad range of crime types, they also conclude that existing literature lacks depth. These authors predict “a change of direction might be observed, with the generation and quantitative analysis of multiple and more detailed scripts (that is, tracks) for each crime type” (p. 15).…”
Section: Review Of Relevant Literaturementioning
confidence: 98%
“…Cognitive science has employed script analysis since at least the 1970s (see Abelson, 1976; Schank & Abelson, 1977), and crime scripts have since emerged as a key analytical tool in the field of criminal justice. A recent systematic review by Dehghanniri and Borrion (2019) has shown that crime scripting has been especially popular over the past 5 years, with 52% of the 416 identified articles published since 1994 being published between 2014 and 2018. Dehghanniri and Borrion identified 105 original scripts within the 416 articles.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…A systematic review by Dehghanniri and Borrion (2019) of crime types covered by 105 crime scripts (a concept elaborated in the next section) from 1994 to 2018 revealed that the highest number of crime scripts have been constructed for cybercrime, followed by corruption and fraud offences, robbery and theft offences, and the lowest number for sexual offences. Unlike the more extensive crime scripting of pure cybercrime/cyberfocused crime (where the targets are data, computers, networks or similar) and traditional crime in the offline world, crime scripting of cyber-enabled/technology-facilitated/cyber-dependent crime is scant, as is scripting of cyber-enabled/technology-facilitated/cyber-dependent sexual crime.…”
Section: Introductionmentioning
confidence: 99%